Pemanfaatan Limbah Kelapa (Cocos Nucifera) dalam Pembuatan Briket Sebagai Upaya Peningkatan Perekonomian Masyarakat di Desa Kelambir Kecamatan Pantai Labu Kabupaten Deli Serdang - Jamilah Nasution; Ferdinand Susilo; Rahmiati Rahmiati; Agung Suharyanto (Universitas Medan Area, 2022)
Coconut waste can be processed into briquettes that can be reused as an alternative fuel that is environmentally friendly. Brickets are blocks of material that can be used as fuel to start and maintain a fire. Kelambir Village, Pantai Labu District, Deli Serdang Regency is one of the villages that has the most coconut plantations and most of the people use coconut plants that grow around it. Kelambir village is known as one of the coconut producing areas, but it has not been used optimally. Therefore, it is necessary to increase understanding and awareness about processing coconut shell brickets through public education in order to increase the value of waste and increase people's income. This training includes the stages of burning, milling/kneading, molding and drying to make charcoal brickets from coconut shells.